KEDUDUKAN TAKLIK TALAK MENURUT HUKUM FIKIH DAN KOMPILASI HUKUM ISLAM - Hibnu Nugroho (Al-Bayyinah, 2018)
The fundamental difference between Jurisprudence Law and Islamic Law Compilation regarding Taklik Talak in Jurisprudence Law and Compilation of Islamic Law According to Fiqh Law is explained in Ahwal Asyakhsiyyah and other book sources states that if taklik talak is violated by the husband, divorce will automatically fall without the consent of the husband and without a verdict from the court Religion and falling talaq are triple divorce. In contrast to the Compilation of Islamic Law mentioned in Article 45 and Article 46, it is explained that divorce falling from Taklik Talak violations can only occur in front of the Religious Court Session with the stipulation that taklik talak is truly pronounced and signed by the husband as authentic evidence that the husband is right violating his divorce pledge and as a judge's judgment in determining his decision.